2018
DOI: 10.1055/s-0038-1675589
|View full text |Cite
|
Sign up to set email alerts
|

Approach Selection and Surgical Planning in Posterior Cranial Fossa Meningiomas: How I Do It

Abstract: Posterior cranial fossa meningiomas represent approximately 9% of all the intracranial meningiomas. Despite the recent reports of radiation therapy in the management of these tumors, surgical resection continues to be the first line of treatment method aiming the permanent meningioma eradication. The evolution of imaging studies improved the preoperative evaluation of meningiomas providing greater anatomical detail of small structures not previously visualized. Nonetheless, the preoperative radiological evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Sometimes, PCMs may also displace CN V laterally and superiorly, CN VI laterally and posteriorly, CNs VII/VIII, IX/X/XI posteriorly, CN XII posterior and inferiorly, and the brainstem posteriorly. 1,22 We were unable to expose the Meckel cave due to preservation of the petrous apex. The other limitation is that tumor extending into the cavernous sinus cannot be exposed and resected as shown in ►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, PCMs may also displace CN V laterally and superiorly, CN VI laterally and posteriorly, CNs VII/VIII, IX/X/XI posteriorly, CN XII posterior and inferiorly, and the brainstem posteriorly. 1,22 We were unable to expose the Meckel cave due to preservation of the petrous apex. The other limitation is that tumor extending into the cavernous sinus cannot be exposed and resected as shown in ►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Position and skin incision of FLA: The patient was in the lateral prone position, whose head was raised 15° to facilitate the venous return, and the head was forward 10° of flexion and 15° to the side of the neck slightly buckled to make the same side of the temporal bone mastoid and superior nuchal line located at the highest point and to increase the clearance between the foramen magnum and atlas; at the same time, the trouble side shoulder should be pulled in the direction of the feet to increase neck exposure. The head of the patient was fixed on a Mayfield head frame [ 1 ], and an inverted “L”-shaped skin incision started at the junction of the transverse sinus and sigmoid sinus, reached the posterior median line along the superior line, and then stopped at the 3rd and 4th cervical spine processes. The skin and subcutaneous tissue were cut open, and the muscular layers were cut and retracted laterally (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The foramen magnum region is an important passage from the brain to the spinal cord and is the continuation of the central nervous system. It is also the only way through which many blood vessels and peripheral nerves pass and is the main site of some nervous system tumors [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The limits of endoscopic anterior petrosectomy have been later confirmed by the same group [38] who concluded that endoscopic endonasal apicectomy could be an option to treat small intradural lesions. Other authors [11,22,105] have pointed out that the position of cranial nerves should be a key factor when selecting the surgical approach. In true petroclival meningiomas, CN VI is usually displaced medially, thus rendering EEA unsuitable.…”
Section: Endoscopic Endonasal Approachesmentioning
confidence: 99%